HUBUNGAN ANTARA SELF EFFICACY DENGAN PERILAKU BELAJAR DAN MENYONTEK SISWA - Ghea Restu Firdana; Raja Arlizon; Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This research is aimed at 1) To know the description of student self efficacy, 2) To know the description of student's learning behavior, 3) to know the description of student's cheating behavior, 4) to know the correlation between self efficacy and student's learning behavior, 5) to know the relationship between self efficacy and student's cheating behavior. Data collection tools such as questionnaires self eficacy, learning behavior and cheating. Subjects were all students of class X SMK Muhammadiyah 2 Pekanbaru, amounting to 370 people, but researchers only take 50% of the students of class X. The samples using Random Sampling technique. The data analysis was done by using percentage and Pearson product moment correlation. Where the researcher chose class X students because of the results of the phenomenon in the field. The results showed that students who have self efficacy mostly are in the medium category of 62.16%, students who have learning behavior mostly are in good enough category of 57.84% and students who have cheat behavior is almost mostly in the category Rarely 47.57%. There is a positive relationship between self efficacy and student learning behavior. This is evidenced by the correlation value of 0.511 and the value of p = 0.00. There is a negative relationship between self efficacy and student cheating behavior. This is evidenced by the correlation value of -0.514 and the value of p = 0.00.Keywords: Self Efficacy, Learning Behavior and Cheat Behavior